A H-bond strategy to develop acid-resistant photoswitchable rhodamine spirolactams for super-resolution single-molecule localization microscopy. Issue 18 (11th April 2019) - Qi, Qingkai; Chi, Weijie; Li, Yuanyuan; Qiao, Qinglong; Chen, Jie; Miao, Lu; Zhang, Yi; Li, Jin; Ji, Wei; Xu, Tao; Liu, Xiaogang; Yoon, Juyoung; et al.
Abstract : Rhodamine spirolactams with adjacent amino groups work as acid-resistant and photoswitchable fluorophores in single-molecule localization super-resolution imaging. Abstract : Rhodamine spirolactam based photoswitches have been extensively applied in super-resolution single-molecule localization microscopy (SMLM). However, the ring-opening reactions of spirolactams are cross-sensitive to acid, limiting their photoswitch use to neutral pH conditions. In addition, the ring-closing reactions of spirolactams are environment-sensitive and slow (up to hours), virtually making rhodamine spirolactams caged fluorescent dyes instead of reversible photoswitches in SMLM. Herein, by introducing hydrogen bonds to stabilize spirolactams, we report a series of acid-resistant rhodamine spirolactams with accelerated ring-closing reactions from fluorescent xanthyliums to non-fluorescent spirolactams, endowing them with good photoswitchable properties even in acidic environments. By further substitution of 6-phenylethynyl naphthalimide on the spirolactam, we shifted the photoactivation wavelength into the visible region (>400 nm). Subsequently, we have successfully applied these dyes in labeling and imaging the cell surface of Bacillus subtilis at pH 4.5 using SMLM.